ANALISIS PENAWARAN BERAS PROVINSI SUMATERA UTARA - Joko Suharianto (Quantitative Economics Journal, 2017)
Financial inclusion programs in Asia began to intensify with focus on improving public access, especially those who have not yet enjoyed banking services. This makes financial inclusion one of the focuses of development in the financial sector in various countries, especially ASEAN, as a sound financial system can promote economic growth. This study aims to see the comparison of financial inclusion rates and see the effect of socio-economic variables on  financial inclusion in  ASEAN  countries 2010-2015. In  order  to  see  the comparison of inclusion level of finance in each ASEAN country, the Index of Financial Inclusion (IFI) method was developed by Sarma (2008), while to examine the relationship between socio-economic variables to financial inclusion, the Ordinary Least Square (OLS) method was used estimation techniques in the Random Effects Model approach. The results show that in general, financial inclusion in ASEAN countries is mainly influenced by the dimension of a disorder. In addition, only per-capita GDP variables are not significant partially. While other variables, namely population over 15 years, unemployment rate, and the number of people in rural areas have a significant influence on index of financial inclusion